2020
DOI: 10.1038/s41583-020-0287-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of subcortical shortcuts on disordered sensory and cognitive processing

Abstract: The very earliest stages of sensory processing have the potential to alter how we perceive and respond to our environment. These initial processing circuits can incorporate subcortical regions, such as the thalamus and brainstem nuclei, which mediate complex interactions with the brain's cortical processing hierarchy. These subcortical pathways, many of which we share with other animals, are not merely vestigial but appear to function as 'shortcuts' that ensure processing efficiency and preservation of vital l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 206 publications
(239 reference statements)
7
49
0
Order By: Relevance
“…Such cellular changes likely impact on the functional organization of cortical microcircuits in autism, also suggested by molecular studies in animals 4,[22][23][24][25]85,86 . These findings collectively support the imbalance in excitation and inhibition of cortical areas in autism 4,9,16,22,87,88 , which have been related to anomalies in cortical neurotransmitter systems [89][90][91][92] and atypical subcortico-cortical interactions with subcortical structures such as thalamus modulating this balance 7,11,24,74,75,93 . Here, we obtained support for perturbations in cortical microcircuit function from a network perspective, by leveraging a biophysically plausible computational model of brain function, which seeks to tune parameters to optimize the link between structural and connectomes 18 .…”
Section: Discussionsupporting
confidence: 71%
“…Such cellular changes likely impact on the functional organization of cortical microcircuits in autism, also suggested by molecular studies in animals 4,[22][23][24][25]85,86 . These findings collectively support the imbalance in excitation and inhibition of cortical areas in autism 4,9,16,22,87,88 , which have been related to anomalies in cortical neurotransmitter systems [89][90][91][92] and atypical subcortico-cortical interactions with subcortical structures such as thalamus modulating this balance 7,11,24,74,75,93 . Here, we obtained support for perturbations in cortical microcircuit function from a network perspective, by leveraging a biophysically plausible computational model of brain function, which seeks to tune parameters to optimize the link between structural and connectomes 18 .…”
Section: Discussionsupporting
confidence: 71%
“…Our results may provide further evidence for subcortical "short-cuts" for sensory and cognitive processing 36 , such as fear or threat. Previously 23 we proposed that rapid subcortical routes for threat processing may be recruited during the act of self-criticism or self-hatred, given the brain may utilize similar routes for processing both physical and social pain 37 , but importantly from empirical work which has found an association between amygdala processing and lingual gyrus activation during threat processing 38 .…”
Section: Discussionmentioning
confidence: 52%
“…Thus, orientation column-like structures have been Review identified in the SC of rodents 36,37 , although these have not been evident in all studies 208 . Furthermore, face-selective SC neurons have been found in primates 209,210 , and the SC has been implicated in processing aversive image and face recognition in primates, including humans [210][211][212][213] . It has also been reported that some blindsight patients can detect facial expressions, a phenomenon called 'affective blindsight' 67 , further suggesting that roles traditionally viewed as cortical can also be performed in the tectum/SC.…”
Section: Discussionmentioning
confidence: 99%